Hypoxia enhances cholangiocarcinoma invasion through activation of hepatocyte growth factor receptor and the extracellular signal-regulated kinase signaling pathway - VANICHAPOL, THITINEE (Mol Med Rep, 2015)
Hypoxia is associated with tumor progression and poor prognosis in several cancer types. The present study aimed to examine the contribution of hypoxia (1% O(2)) to cancer progression in a cholangiocarcinoma cell line, RMCCA-1. The molecular basis of the hypoxic response pathway was investigated. The results showed that hypoxia significantly accelerated cancer cell proliferation and enhanced cell invasion (P<0.05). By using receptor tyrosine kinase and intracellular signaling antibody array kits, an increased phosphorylation/activation of a number of signaling molecules, particularly hepatocyte growth factor receptor (Met) and extracellular signal-regulated kinase (ERK) 1/2, was identified. Inhibition of Met and ERK by small hairpin RNA and U0126, respectively, significantly inhibited hypoxia-induced the invasive potential of RMCCA-1 cells (P<0.05). However, according to immunohistochemical analysis, hypoxia-inducible factor-1α expression was not correlated with cancer staging or tumor differentiation in 44 samples of cholangicarcinoma cases. The findings of the present study emphasized the importance of Met/ERK pathway activation as a key molecular event that may be responsible for a more invasive phenotype in hypoxic tumors and suggest Met as a potential target for the treatment of cholangiocarcinoma.